Serum Catestatin Concentrations Are Increased in Patients with Atrial Fibrillation - Josip Katic; Zrinka Jurisic; Marko Kumric; Josip A. Borovac; Ante Anic; Toni Breskovic; Daniela Supe-Domic; Josko Bozic (Journal of Cardiovascular Development and Disease, 2023)
The autonomic nervous system is crucial in initiating and maintaining atrial fibrillation (AF). Catestatin is a multipurpose peptide that regulates cardiovascular systems and reduces harmful, excessive activity of the sympathetic nervous system by blocking the release of catecholamines. We aimed to determine whether serum catestatin concentrations are associated with AF severity, duration indices, and various clinical and laboratory indicators in these individuals to better define the clinical value of catestatin in patients with AF. The present single center study enrolled 73 participants with AF and 72 healthy age-matched controls. Serum catestatin concentrations were markedly higher in AF patients than controls (14.11 (10.21–26.02) ng/mL vs. 10.93 (5.70–20.01) ng/mL, p = 0.013). Furthermore, patients with a more severe form of AF had significantly higher serum catestatin (17.56 (12.80–40.35) vs. 10.98 (8.38–20.91) ng/mL, p = 0.001). Patients with higher CHA2DS2-VASc scores (17.58 (11.89–37.87) vs. 13.02 (8.47–22.75) ng/mL, p = 0.034) and higher NT-proBNP levels (17.58 (IQR 13.91–34.62) vs. 13.23 (IQR 9.04–22.61), p = 0.036) had significantly higher serum catestatin concentrations. Finally, AF duration correlated negatively with serum catestatin levels (r = −0.348, p = 0.003). The results of the present study implicate the promising role of catestatin in the intricate pathophysiology of AF, which should be explored in future research.